Treading carefully: a qualitative ethnographic study of the clinical, social and educational uses of exercise ECG in evaluating stable chest pain. Issue 1 (8th February 2012) - Cramer, Helen; Evans, Maggie; Featherstone, Katie; Johnson, Rachel; Zaman, M Justin S; Timmis, Adam D; Hemingway, Harry; Feder, Gene
Abstract : Objective: To examine functions of the exercise ECG in the light of the recent National Institute for Health and Clinical Excellence guidelines recommending that it should not be used for the diagnosis or exclusion of stable angina. Design: Qualitative ethnographic study based on interviews and observations of clinical practice. Setting: 3 rapid access chest pain clinics in England. Participants: Observation of 89 consultations in chest pain clinics, 18 patient interviews and 12 clinician interviews. Main outcome measure: Accounts and observations of consultations in chest pain clinics. Results: The exercise ECG was observed to have functions that extended beyond diagnosis. It was used to clarify a patient's story and revise the initial account. The act of walking on the treadmill created an additional opportunity for dialogue between clinician and patient and engagement of the patient in the diagnostic process through precipitation of symptoms and further elaboration of symptoms. The exercise ECG facilitated reassurance in relation to exercise capacity and tolerance, providing a platform for behavioural advice particularly when exercise was promoted by the clinician. Conclusions: Many of the practices that have been built up around the use of the exercise ECG are potentially beneficial to patients and need to be considered in the re-design of services without that test. Through its contribution to the patient's history and to subsequent advice to the patient, the exercise ECG continues to inform the specialist assessment and management of patients with new onset stable chest pain, beyond its now marginalised role in diagnosis.